Impact of sports participation on the occurrence of musculoskeletal pain in adolescents during 28 weeks of follow-up: ABCD Growth Study - Maillane Vanegas, Santiago [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
This thesis aimed to explore the association between sports participation and incidence of pain among adolescents in a 28-week follow-up period, as well as to identify the role of sex, biological maturation and training volume into this phenomenon. This longitudinal design of 28 weeks followed 95 adolescents, subdivided according to the presence or absence of participation in sports and the modality practiced, consequently, the groups were: adolescents from non-impact sports, impact sports, and non-sports groups, following the inclusion criteria. They reported the occurrence of pain and were tracked weekly by the research team, “the presence of any pain in the previous 7 days” was self-reported weekly. Anthropometric data such as height and sitting height were collected to estimate as a marker of somatic maturation in a mathematical model, and body composition data was also collected through DXA. The data distribution was analysed using Kolmogorov-Smirnov, and variables were expressed as mean values, standard deviation (SD), and 95% confidence intervals. The significance level was set as 5%. The findings indicate that the association between the sport type and pain occurrence remained significant even after adjusting the models by sex and maturity offset, swimmers had an increased risk of reporting pain neck, shoulders, and trunk pain, compared to the impact sport group, mainly caused by the high volume of practice in the modality. Also, the weekly time spent on sports at vigorous intensity is related to a higher occurrence of pain, adjusted by lean soft tissue, sport modality, and sedentary behaviour. Thus, this thesis presents innovative aspects in the development and implementation of a pain surveillance system related to the adolescent growth and development process, finding that the relationship between pain continues to have a close relationship with sports participation, even considering the somatic growth factor adjustment variable. The volume of training seems to be the most relevant variable in this phenomenon and there exists a limit to how much they should engage in sports to preserve their health. In addition, the vigorous intensity at which said activity is carried out further accentuates the occurrence of pain.

Esta tese teve como objetivo explorar a associação entre participação esportiva e incidência de dor entre adolescentes em um período de acompanhamento de 28 semanas, bem como identificar o papel do sexo, maturação biológica e volume de treinamento neste fenômeno. O delineamento longitudinal de 28 semanas acompanhou 95 adolescentes, subdivididos de acordo com a presença ou ausência de participação em esportes e a modalidade praticada, consequentemente, os grupos foram: adolescentes de esportes sem impacto, esportes de impacto e grupos não esportivos, seguindo os critérios de inclusão. Eles relataram a ocorrência de dor e foram monitorados semanalmente pela equipe de pesquisa, “a presença de qualquer dor nos 7 dias anteriores” autorrelatada semanalmente. Dados antropométricos como altura e altura sentada foram coletados para estimar como um marcador de maturação somática em um modelo matemático, e dados de composição corporal também foram coletados por DXA. A distribuição dos dados foi analisada usando Kolmogorov-Smirnov, e as variáveis foram expressas como valores médios, desvio padrão (DP) e intervalos de confiança de 95%. O nível de significância foi definido como 5%. Os achados indicam que a associação entre o tipo de esporte e a ocorrência de dor permaneceu significativa mesmo após o ajuste dos modelos por sexo e desvio de maturidade, os nadadores apresentaram risco aumentado de relatar dor no pescoço, ombros e tronco, em comparação ao grupo de esporte de impacto, causado principalmente pelo alto volume de prática na modalidade. Além disso, o tempo semanal gasto em esportes de intensidade vigorosa está relacionado a uma maior ocorrência de dor, ajustado por tecido mole magro, modalidade esportiva e comportamento sedentário. Assim, esta tese apresenta aspectos inovadores no desenvolvimento e implementação de um sistema de vigilância da dor relacionado ao processo de crescimento e desenvolvimento do adolescente, constatando que a relação entre dor continua a ter estreita relação com a participação esportiva, mesmo considerando a variável de ajuste como fator de crescimento somático. O volume de treinamento parece ser a variável mais relevante neste fenômeno e existe um limite para o quanto eles devem se envolver em esportes para preservar sua saúde. Além disso, a intensidade vigorosa em que tal atividade é realizada acentua ainda mais a ocorrência de dor.
Impacto da participação esportiva na ocorrência de dor musculoesquelética em adolescentes durante 28 semanas de acompanhamento: estudo ABCD crescimento
Keywords: Multisite pain; Adolescents health; Sports for youths; Maturity offset; Musculoskeletal disorder; Dor multissítio; Saúde do adolescente; Esportes para jovens; Deslocamento de maturidade; Distúrbio musculoesquelético